PENGARUH PEMBERIAN AROMATERAPI PEPPERMINT TERHADAP FREKUENSI MUAL MUNTAH PADA IBU HAMIL TRIMESTER 1 - Untari Anggeni; Vera Yuanita; Bella Syapira (Jurnal Kesehatan dan Pembangunan, 2026)
Based on data from the World Health Organization (WHO, 2023), the incidence of emesis gravidarum is at least 15% of all pregnant women. 8 The incidence of nausea, vomiting or morning sickness in the world is 70-80% of the number of pregnant women. Emesis gravidarum occurs throughout the world with varying incidence rates, namely 1-3% of all pregnancies in Indonesia, 0.9% in Sweden, 0.5% in California, 1.9% in Turkey, and in the United States the prevalence of emesis gravidarum as much as 0.5%-2%. The incidence of emesis gravidarum in Indonesia, obtained from 2,203 pregnancies that were completely observed, was 543 pregnant women affected by emesis gravidarum. In Indonesia, around 10% of pregnant women are affected by emesis gravidarum. The aim of this study was to determine the effect of giving peppermint aromatherapy on the intensity of nausea and vomiting in pregnant women in the first trimester. The population of this study was all pregnant women in the first trimester who experienced nausea and vomiting who came to PMB Ferawati at the time the research was conducted. The results of the research showed that there was an effect of giving Peppermint Aromatherapy from the results of the Prestest Data (p.valau = 0.085) where there was an effect of giving Peppermint Aromatherapy on the Frequency of Nausea and Vomiting, and the results of the Posttest Data research (p.valau = 0.001) showed an influence from giving Peppermint Aromatherapy against the frequency of nausea and vomiting.